Teknik Pemeriksaan Cystografi pada Kasus Fistule Vesicorectal di Instalasi Radiologi RS Efarina Etaham Berastagi - Purba, Juni Sinarinta; Sitohang, Putra Raja P P; Siahaan, Nopita Sari (Prosiding Seminar Kesehatan Nasional, 2022)
Cystography is a radiographic examination to visualize the vesica urinaria using positive contrast media administered retrogradely through a catheter. Vesicorectal fistula is an abnormal channel connecting the urinary bladder with the rectum. This case study was conducted at the Radiology Installation of RS Efarina Etaham Berastagi on a 51-year-old male patient with suspected vesicorectal fistula. The examination used projections of AP plain, AP post-contrast, RPO, LPO, lateral, lateral double contrast, and AP post-evacuation. The examination technique used positive contrast media (Iopamidol:aquades ratio 1:4) followed by negative contrast media (air 100cc) administered retrogradely through a catheter. Double contrast technique showed smooth vesica urinaria walls with contrast entering the rectum, and air visible between the rectum and the vesica urinaria posteroinferior, confirming vesicorectal fistula. The use of double contrast (positive and negative) in cystography examination is effective for diagnosing vesicorectal fistula by providing density differences that clearly demonstrate the presence of fistula.